The Combination of Manned and Unmanned Combat Aircraft (UCAV) as a Collaborative Combat Operations to Strengthen Indonesia’s Air Defense System - Prasetiyo, Riyan Eko; Bura, Romie Oktovianus; Amperiawan, Gita; Nainar, Muhammad; Yusuf, Sezsy Yuniorrita; Afriyanto, Ony (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Airspace violations that occur in Indonesia are a form of threat to state sovereignty, national security, and national safety. The violations are actions taken by foreign military and civilian aircraft that enter the country’s territory without permission. Therefore, a strong national air defense system is needed. Ambush fighters with fast reaction capabilities are one of the main elements in a strong national air defense system. The fighter ambush mission can be accompanied by stealth unmanned aircraft technology similar to fighter aircraft, namely Unmanned Combat Aircraft (UCAV), as a Collaborative Combat Aircraft (CCA) mission. This mission collaborates with fighter aircraft and UCAVs to achieve air defense system dominance. In applying the mission, a concept of operation is needed as a guide in carrying out air defense operations. Therefore, this research aims to develop a concept of operations that combines fighter aircraft and UCAVs. The operation concept is developed based on the doctrine of the Air Force and the defense industry, through structured interview methods, forum group discussions, and literature studies. The results showed that collaboration between fighter aircraft and UCAV can fulfill future combat. The proposed operational capability consists of a new generation of unmanned aircraft focusing on collaborative missions and flying alongside 4.5-generation or later manned fighters. The Combat Air Patrol (CAP) concept of operations is one option for collaboration between fighters and UCAVs, with cruise, interception, and air superiority phases. Collaboration is carried out with the division of tasks between fighters and UCAVs. In conclusion, the concept of operations by combining fighter aircraft and UCAV can be applied in Indonesia’s air defense system, to create a strong national defense system.